Реінжиніринг комунікативної та організаційно-економічної систем засобами діджиталізації за умов детерміновасті зовнішнього середовища - Kobelia, Zoriana; Ksjondz, Sergiy; Melnyk, Yaroslav (My University, 2021)
У роботі системно досліджено тематику реінжинірингу організаційно-економічної та комунікативної системи цифровими та технічними засобами в умовах детермінованості зовнішнього середовища, адже із збільшенням інтенсивності глобалізаційних процесів, доступності технологій та швидкості передання інформації, зростає і рівень детермінованості зовнішнім середовищем економічних процесів у бізнесі. Відтак впроваджуючи все нові і нові потрібні digital-інструменти у діяльність компанії, можна згладжувати, адаптовуватись та пристосовуватись до надмірної динамічності факторів зовнішнього середовища, зменшувати витрати чи покращувати формальну та неформальну інституційну взаємодію зі споживачами. Було виокремлено теоретико-методичні основи реінжинірингу організаційно-економічної та комунікативної систем під впливом факторів зовнішнього середовища, зокрема виділено основні парадигми бачень щодо впливу факторів зовнішнього середовища на підприємство. Синтезуючи ідеї цих теорій, запропоновано комплексно оцінювати поточні проблеми організацій та перспективи нововведень, більш чітко добирати цифрові та технічні інструменти digital-трансформації. Виходячи з досліджених концепцій та ознайомившись із сучасними напрямами та тенденціями digital-нововведень, було виокремлено конкретні напрями реінжинірингу організаційно-економічної та інформаційно-комунікативної системи засобами діджиталізації. Конкретне виокремлення пропозицій щодо напрямів реалізовувалось із врахуванням поглядів щодо групування та класифікації елементів згадуваних систем підприємства. Реалізація такого інституційного механізму дає змогу виокремлювати навіть найдрібніші мікропроцеси, які потребують перебудови чи оптимізації за допомогою цифрових та технічних засобів.
REENGINEERING OF COMMUNICATIVE AND ORGANIZATIONAL-ECONOMIC SYSTEMS BY MEANS OF DIGITALIZATION UNDER CONDITIONS OF DETERMINISM OF THE EXTERNAL ENVIRONMENT
The topic of reengineering of organizational-economic and communication system by digital and technical means in the conditions of environmental determinism is systematically studied in the work. Therefore, by introducing more and more necessary digital tools into the company's activities, it is possible to smooth, adapt and adapt to the excessive dynamics of environmental factors, reduce costs or improve formal and informal institutional interaction with consumers. Theoretical and methodological bases of reengineering of organizational-economic and communicative systems under the influence of environmental factors were singled out, in particular, the main paradigms of visions on the influence of environmental factors on the enterprise were identified. Synthesizing the ideas of these theories, it is proposed to comprehensively assess the current problems of organizations and the prospects of innovation, more clearly select digital and technical tools of digital transformation. Based on the researched concepts and getting acquainted with modern directions and tendencies of digital innovations, specific directions of reengineering of organizational-economic and information-communicative system by means of digitalization were singled out. The specific selection of proposals for areas was implemented taking into account the views on the grouping and classification of elements of the mentioned systems of the enterprise. It was revealed in the course of the research that there are a number of factors that negatively affect the prospects of enterprises and digitalization of their activities. As a rule, these are negative recessive economic processes in the country, the specifics of the region of location and mostly a high level of depreciation of fixed assets. Establishing the direction of digitalization in the strategy of enterprise development gives significant advantages over their conventional competitors, especially in today's crisis. The implementation of such an institutional mechanism makes it possible to identify even the smallest microprocesses that need to be rebuilt or optimized using digital and technical means.
Keywords: середовище функціонування; комунікативна; організаційно-економічна системи; реінжиніринг; діджиталізація; operating environment; communication; organizational and economic systems; reengineering; digitalization